The Phenomenon Of Self-Medication Of Analgesic In Patients With Toothache In Batudaa District, Gorontalo Regency, Indonesia - Sitanaya, Rini; Lesmana, Hans; Septa, Badai; Irayani, Surya; Asriawal, Asriawal; Thioritz, Erni; Ningtyas, Endah Aryati Eko; Benyamin, Benni; Prasko, Prasko (Jurnal Kesehatan Gigi, 2025)
Self-medication is an act of self-treatment performed by the community to overcome toothache. Many people who suffer from toothache choose to self-medicate with pain killers or herbal medicines. The phenomenon of self-medication arose because people felt that self-medication was an easier and more practical option than going to the dentist. The aim of the study was to determine the factors that influence the self-medication behaviour of patients with toothache in the community. The research method used was descriptive observational with a cross-sectional approach. The population in this study was the community of Batudaa district, and the sample was taken through accidental sampling method using questioner by google form. The results showed that majority of the respondents (91.66%) had practiced self-medication, 33.97% of them used chemical drugs while 41.02% combined chemical and herbal drugs. Mefenamic acid was the most commonly purchased analgesic from the pharmacy (33.97%), while saline solution was the most commonly used herbal medicine (42.94%). The main reason for self-medication by respondents was convenience and practicality (33.33%), followed by experience of recovery with the same medicine (30.76%), and several other reasons were given by respondents. This study found that personal knowledge and previous experience by themselves or peers significantly influenced the choice of medication, including easier, quicker and can be done by themselves, save cost, time and can return to activities immediately. The conclusion of this study emphasises that self-medication behaviour is influenced by convenience and practicality factors, with recommendations for the community to increase knowledge about the use of analgesics and to consult medical personnel before initiating any medication regimen and symptoms do not improve.